«Նոր Հայկազյան Բառարան»-ի Նորայր Բյուզանդացու խմբագրությունը - Հարությունյան, Խաչիկ
Norayr Byuzandats‘i was one of the famous Armenian philologists and lexicographers of the late 19th and early 20th centuries, a member of the Mekhitharist Congregation in Venice, keeper of the congregation library, editor of the scholarly journal Bazmavēp, and lecturer at the Moorad Raphael College in Venice. Byuzandats‘i’s contribution is particularly significant in Armenian lexicology and lexicography. Unfortunately, his academic legacy still remains insufficiently studied and underappreciated. During his lifetime, he was able to publish only few works, and many of his studies remain unpublished. Норайр Бюзандаци – один из известных деятелей армянской филологии и лексикографии конца XIX и начала XX веков, член конгрегации Мхитаристов Венеции, хранитель библиотеки конгрегации, ответственный редактор научного журнала “Bazmavēp”, и, наконец, преподаватель в колледже Мурада Рафаэля в Венеции.
Keywords: Հայոց լեզվի պատմություն; Պատմական բառագիտություն